Effect of Fermented Mulberry Leaves on Gut Health of Finishing Pigs - Su Peng; Yiyan Cui; Miao Yu; Min Song; Zhimei Tian; Dun Deng; Zhichang Liu; Xianyong Ma (Animals, 2024)
This study was conducted to investigate the effects of supplementing fermented mulberry leaves (FML) on intestinal morphology, antioxidant capacity, and immune function in the gut of finishing pigs. Eighteen 132-day-old healthy crossbred (Duroc × Landrace × Yorkshire) male castrated pigs were randomly divided into two treatment groups with nine replicates per group. The control (CON) group was fed the basal diet, and the FML group was fed the basal diet supplemented with 10% FML. The experiment lasted 69 days. The results showed that 10% FML improved gut health. The apparent total tract digestibility in dry matter, crude protein, crude fiber, neutral detergent fiber, acidic detergent fiber, ether extract, and crude ash increased in the 10% FML group of finishing pigs compared to the CON group (p < 0.05). Duodenal, jejunal, and ileal intestinal morphology, such as villus height and villus-height-to-crypt-depth ratio, increased in the 10% FML group compared to the CON group, whereas crypt depth decreased in the duodenum, jejunum, and ileum (p < 0.05). Total antioxidant capacity increased in the ileum of the 10% FML group compared with the CON group (p < 0.05). The FML supplementation improved the contents of duodenal immunoglobulin A, jejunal interleukin-1β, interleukin-8, ileal interleukin-1β, interleukin-6, interferon-γ, and immunoglobulins A and M compared to the control group (p < 0.05). Moreover, FML downregulated the mRNA expression levels of tumor necrosis factor-α in the duodenum, Toll-like receptor 4, nuclear factor-κ B-P65, and myeloid differentiation factor 88 in the jejunum, and Toll-like receptor 4 and nuclear factor-κ B-P65 in the ileum (p < 0.05). The FML also upregulated Montrose uniting church 1 in the duodenum and claudin 2 in the ileum (p < 0.05). In conclusion, dietary supplementation with 10% FML improved the gut health of finishing pigs and FML is a potential feed ingredient for pig breeding.